Possible Role of High Temperature and Soil Biological Fertility on Kiwifruit Early Decline Syndrome - Bardi, Laura; Nari, Luca; Morone, Chiara; Faga, Maria Giulia; Malusà, Eligio (Frontiers in Agronomy, 2020)
Kiwifruit early decline syndrome is a widespread disorder that affects worldwide kiwifruit orchards. During the last few years, the seriousness and diffusion of this disorder worsened; as a consequence, in several rural areas the economic sustainability of farms was seriously affected. The early symptoms involve leaves (epinasty, chlorosis, desiccation, and abscission), fruits (decrease of number, size, and sugar content), and roots (anomalous morphology and anatomy). After symptoms occurrence, in a short time plants collapse and die: frequently this happens in the same or in the following year. Even though several phytopathological or agronomical studies have been carried out, a clear and univocal explanation of the causes and the possible remedies are yet to be understood. A field trial was carried out in an experimental kiwifruit orchard, in which several soil management practices (ridging, amendment with compost, bioinoculation with selected rhizospheric microorganisms) were tested to evaluate their effect on early decline symptoms occurrence. The analysis of plant growth parameters, root morphology and anatomy, and symptoms onset were related to environmental data (air and soil temperature, soil water tension). The results pointed to a possible role and interaction between agronomic soil management and climatic conditions as the triggering factors of kiwifruit early decline syndrome.